PENGARUH FREKUENSI PEMBERIAN PAKAN TERHADAP SINTASAN DAN PERTUMBUHAN KEPITING BAKAU (Scylla serrata) YANG DIPELIHARA SISTEM SILVOFISHERY - Hartanti, Ninik Umi; Dina, Karina Farkha; Septriono, Wahyu Adi (Universitas Pancasakti Tegal, 2023)
Mangrove crab is one of the fishery commodities that has high economic value and gets a lot of demand from local, regional and foreign markets. This study aims to determine the frequency of appropriate feeding on the survival and growth of mangrove crabs (Scylla serrata) reared by the silvofishery system. This research was conducted from April to May 2021 in the mangrove area of Randusanga District, Brebes Regency, Central Java. The research container used was cages made of bamboo measuring 50 cm x 50 cm x 70 cm in length, width and height, which were placed in the mangove area. The feed used was trash fish in the form of chopped trash fish with a dose of 5% of the crab biomass. This study used a completely randomized design (CRD) with 4 treatments and each treatment had 3 replications. The treatments tested were 2 times a day, 1 time a day, 1 time 2 days and 1 time 3 days. The data obtained were analyzed using analysis of variance (ANOVA) and further W-Tuckey test. The results showed that the frequency of feeding was not significantly different (p > 0.05) in the survival and growth of mud crabs reared by the silvofishery system. The water quality in the study supports the growth and survival of mangrove crabs during the study is still suitable for cultivation of mud crabs (Scylla serrata).